Role of Disclosing Psychological Distress and Intention to Seek Counseling in the Relationship Between Attitude, Stigma and Working Alliance: A Conceptual Paper - Siti Nurafif Naim; Chua, Bee Seok; Muhammad Idris Bullare @ Bahari; Patricia Joseph Kimong (Psychology and Social Health Research Unit, 2022)
Various psychotherapeutic approaches have acknowledged the crucial component of working alliance in the helping relationship. Utilization of counseling service by university students is very low despite easy accessibility with minimal or no fees. Avoidance of counseling, even when a student may benefit from it, may lead to unattended psychological problems that are likely to affect their academic achievement. If a student does enter counseling, the counselor has an important role to ensure a strong working alliance in the relationship. The working alliance component is fundamental in the helping process to facilitate better life outcomes for clients. Ruptures in the working alliance may lead to reduced motivation to return to counseling. While attitude and stigma are known factors associated with counseling avoidance among university students in the Malaysian context, the three working alliance components based on Bordin’s (1979) working alliance conceptualization have not been adequately examined. The three components to the working alliance concept are as follows: (i) Goal; (ii) Task; and (iii) Bond. This conceptual paper discusses the working alliance and the role of distress disclosure and intention to seek counseling in the relationship between attitude and stigma amongst university students seeking professional psychological help in Malaysia. The Theory of Reasoned Action is the main theoretical framework referred in guiding the discussion of this conceptual paper.